Efeito da temperatura no desenvolvimento e sobrevivência da cochonilha pseudococcus longispinus (Targioni Tozzetti, 1867) (hemiptera: Pseudococcidae) em cafeeiro - Santa-Cecília, Lenira Viana Costa; Prado, Ernesto; de Sousa, Marcella Viana; de Sousa, Ana Luiza Viana; Correa, Lilian Roberta Batista [UNESP] (My University, 2011)
The longtailed mealybug Pseudococcus longispinus (Targioni Tozzetti, 1867) (Hemiptera: Pseudococcidae) has been reported attacking coffee crops causing fruit fall in the State of Minas Gerais, Brazil. The knowledge of the population dynamic of this pest is then necessary to implement control measures. Its development was studied at temperatures of 15, 20, 25, 30 and 35°C, determining the thermal requirements. The insects were confined inside a Petri dish containing a foliar disc of 4 cm diameter of Coffea arabica L., cultivar 'Acaiá Cerrado'. The temperature affected the P. longispinus development and survival. Few insects survived at temperatures of 15 and 30°C, and 100% of mortality was obtained at 35°C. The duration of the nymphal stage was reduced when the temperature was increased from 20 to 25°C, with a survival rate of 80% at both temperatures. The thermal parameters varied according to the development stage of the mealybug and the base temperature was fixed at 8.0 °C for the nymphal stage of females, a thermal constant of 422.1 day degrees and number of generations increased with rising temperature. The optimal temperature for the insect development was 25°C.
Effect of temperature on the development and survival of the longtailed mealybug pseudococcus longispinus (Targioni Tozzeti, 1867) (Hemiptera: Pseudococcidae) in coffee plants
Keywords: Biology; Coccoidea; Coffea arabica; Thermal parameters; Hemiptera; Hexapoda; Pseudococcidae; Pseudococcus longispinus